India - Vulnerability of Kolkata metropolitan area to increased precipitation in a changing climate - World Bank (World Bank, 2012)
This study aims to strengthen the understanding of the vulnerability of Kolkata from increased precipitation caused by climate change effects with a specific goal to: compile a data base with past weather related information and damage caused by extreme weather related episodes; develop hydrological, hydraulic, and storm drainage models to identify vulnerable areas and determine physical damage estimates resulting from climate change effects; assess monetary, social, and environmental impacts resulting from such climate change events; and strengthen local capabilities so that the planning process for Kolkata can account for climate related damage effects in future while analyzing all new projects. In this study, precipitation events in Kolkata based on available historical rainfall data for 25 years has been considered as a baseline (without climate change) scenario. The study modeled the impact of climate change on increased flooding in Kolkata Metropolitan Area (KMA). The main causes of flooding in KMA are intense precipitation, overtopping of the Hooghly River due to water inflow from local precipitation as well as that from the catchment area, and storm surge effects. Land subsidence was not included in the study as it was felt to be a localized problem in only a few pockets.